Pengaruh Pemahaman Akuntansi, Sumber Daya Manusia dan Pemanfaatan Teknologi Informasi Terhadap Kualitas Laporan Keuangan: Studi Kasus Badan Usaha Milik Desa di Kecamatan Dawan - Yanthi, Ni Putu Risma; Putu Cita Ayu; Ni Putu Yeni Yuliantari (UNHI Press, 2025)
The aim of this research was to assess how accounting knowledge, How human resources and the use of information technology affect the quality of financial istatements, focusing on Village-Owned Enterprises in Dawan District. The study encompassed all 112 employees of BUMDes in Dawan District, Using purposive sampling, a sample of 42 respondents was selected for the study. Data analysis was conducted through multiple linear regression analysis. The results of this survey demonstrate that accounting knowledge has a positive and statistically significant impact on financial reporting quality. In addition, human resources also show a notable positive influence on financial reporting qualit.. Based on these outcomes, it is envisioned that BUMDes in Dawan Klungkung District can enhance and sustain their accounting knowledge, human resources, and information technology usage to generate high-quality financial reports. These quality financial reports are expected to facilitate decision-making, thereby contributing to the achievement of BUMDes' objectives.